P3-GemOx as a novel immunochemotherapy candidate in NK/T-cell lymphoma management - Zhang, Yuyang; Kou, Haiming; Cheng, Zhipeng; Lu, Xuan; Hu, Yu; Tang, Liang V. (Frontiers in Medicine, 2025)
IntroductionNatural killer/T-cell lymphoma (NKTL) is a rare disease that shows suboptimal responses to existing therapies. This study reports the efficacy of the P3-GemOx regimen compared to the traditional PP-GemOx regimen in advanced NKTL.MethodsEleven patients received the P3-GemOx regimen [mitoxantrone hydrochloride liposome (Plm60) combined with PP-GemOx (anti-PD-1 antibody, pegaspargase, gemcitabine, and oxaliplatin)] every 3–4 weeks, with a median of 3 cycles (range: 1–4). Another eleven patients received the PP-GemOx regimen every 3–4 weeks, with a median of 4 cycles (range: 2–6). Treatment response was assessed using 18F-FDG-PET with CT or MRI.ResultsAll patients treated with P3-GemOx responded, with nine achieving complete remission (CR) and two partial remission (PR), yielding an overall response rate (ORR) of 100%. Seven of these patients underwent hematopoietic stem cell transplantation (HSCT). In the PP-GemOx group, the ORR was 63.6%, and no patients underwent HSCT. All adverse events were manageable and resolved.DiscussionThe P3-GemOx regimen demonstrates superior efficacy over the PP-GemOx regimen in advanced NKTL.